The Curse of the Were-Rabbit : the Monstrously Scary Joke Book - Li, Amanda (Puffin Books, 2005)
You've seen their fearsome film, now join Wallace and Gromit for some seriously scary fun! In this book, the duo present a collection of monstrous jokes based around the characters in the film.
Including Illustration
Keywords: Wallace (Fictitious character) -- Gromit (Fictitious character) -- Wit and humor, Juvenile